The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/lary.22421
|View full text |Cite
|
Sign up to set email alerts
|

A nomenclature paradigm for benign midmembranous vocal fold lesions

Abstract: This study has validated a multidimensional BVFL nomenclature paradigm. This vocal fold nomenclature paradigm includes nine distinct vocal fold lesions: vocal fold nodules, vocal fold polyp, pseudocyst, vocal fold cyst (subepithelial or ligament), nonspecific vocal fold lesion, vocal fold fibrous mass (subepithelial or ligament), and reactive lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 8 publications
(8 reference statements)
3
89
2
Order By: Relevance
“…Clinical diagnoses were based on the appearance of the vocal fold edge and the vibratory property of the mucosa revealed by videolaryngostroboscopy (VLS), based on the published nomenclature and diagnostic paradigm. 1 Vocal nodules were classified as (1) soft (ie, mid-membranous thickening without fibrotic change of the epithelium or limitation of the mucosal wave) or (2) hard (ie, hyperkeratosis of the epithelium, fibrotic appearance with some limitation of mucosal wave propagation). Vocal polyps were classified as hemorrhagic (vascular), fusiform (wide-based), pedunculated, and fibrous.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical diagnoses were based on the appearance of the vocal fold edge and the vibratory property of the mucosa revealed by videolaryngostroboscopy (VLS), based on the published nomenclature and diagnostic paradigm. 1 Vocal nodules were classified as (1) soft (ie, mid-membranous thickening without fibrotic change of the epithelium or limitation of the mucosal wave) or (2) hard (ie, hyperkeratosis of the epithelium, fibrotic appearance with some limitation of mucosal wave propagation). Vocal polyps were classified as hemorrhagic (vascular), fusiform (wide-based), pedunculated, and fibrous.…”
Section: Study Subjectsmentioning
confidence: 99%
“…1 Common clinical presentations of these lesions include dysphonia, voice fatigue, dryness or tightness of voice, narrowed vocal range, and deteriorated voice quality (husky or breathy character). Because most of these patients have an occupational dependence on their voices, noisy working environments, or inappropriate phonation habits; in most circumstances, behavioral modification remains the first-line management, followed by phonomicrosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study sought to find diagnostic concordance for conditions such as benign vocal fold lesions in which there is much disagreement regarding the basic diagnostic criteria. 14,15 For instance, it is unclear whether the diagnostic variability in the present study with vocal fold nodules represents limitations of the imaging modality or the agreement as to the physical appearance of those nodules. Finally, the wide range of diagnostic possibilities engaged multiple levels of variability, which ultimately limits the statistical power of the findings.…”
Section: Discussionmentioning
confidence: 84%
“…The lesions often or typically interfere with the vibratory behaviour of the vocal folds, creating increased aperiodicity which results in symptoms of mild to moderate dysphonia characterised by hoarseness, breathiness, low pitch, and laryngeal hyperfunction; with hoarseness being the most common symptom (Pannbacker, 1999;Verdolini et al, 2006). It has been reported that a key stroboscopic diagnostic feature for vocal fold nodules is normal or minimal impairment of the vibratory properties of the mucosa (Rosen et al, 2012). Also, vocal fold nodules respond favorably to voice therapy and reduced voice demands with either complete resolution or substantive diminution of the size of the lesions.…”
Section: Chapter One 1 Introductionmentioning
confidence: 99%
“…Also, vocal fold nodules respond favorably to voice therapy and reduced voice demands with either complete resolution or substantive diminution of the size of the lesions. Thus, any lesions that do not respond to voice therapy, cannot be vocal fold nodules (Rosen et al, 2012). Vocal fold nodules cause voice difficulties that often lead to lost time at work, reduced productivity and impaired quality of life (Kunduk & McWhorter, 2009).…”
Section: Chapter One 1 Introductionmentioning
confidence: 99%